Identification of the aroma compounds in Vitex doniana sweet: free and bound odorants - Olaniyi, Lasekan Olusegun (Chemistry Central, 2017)
Background: Most often, the glycosidically-bound aroma compounds are released during industrial processing or pre-treatment of fruits. This usually introduces modification to the aroma notes of such fruits. Therefore, there isthe need to understand the contribution of these bound aroma compounds to the overall aroma of a given fruit. In recent years research studies have reported on the free- and bound volatile compounds of several fruits. However, there is no report yet on Vitex doniana sweet. Results: Results of gas chromatography–mass spectrometry (GC–MS) and gas chromatography–olfactometry (GC–O) of free and glycosidically-bound aroma-active compounds from Vitex doniana sweet revealed a total of 35 compounds in the free fraction, and 28 compounds were in the bound fraction respectively. Whilst the major group of compounds in the free fraction were terpenes, alcohols, and esters, the bound fraction consisted of ketones, alcohols, terpenes and norisoprenoids. Conclusion: A comparative analysis of the aroma potencies of the free and bound volatile fractions revealed that; free fraction exhibited strong potency for the fruity and floral notes, and the bound fraction produced more of the flowery, caramel-like and cherry-like notes. In addition results of odour activity values showed that ethylbutanoate, β-damascenone, ethyl-2-methyl propionate, linalool, hexyl acetate and (Z)-rose oxide contributed highly to the sweet prune-like aroma of the fruit.